Analytical Models for the Estimation of Effect of the Spray Angle on a Subcooled Target - Rejus Kumar, Arun V; Francis Britto, A. Sagai (International Journal of Psychosocial Rehabilitation, 2019)
Since its beginnings nearly a century ago, plant superintendents and maintenance personnel have relied on thermal spray technology as a cost-effective means to repair worn components and incorrectly machined parts for light and heavy industrial equipment. The manufactures of thermal spray equipment and materials have continued their efforts to make thermal spray technology more attractive by creating new spray systems and materials. As a result, it is now possible to tailor a coating solution to fit a customer’s needs. Thermal sprayed coatings are used extensively for a wide range of industrial applications. The technique generally involves the spraying of molten powder or wire feedstock, the melting technique achieved by oxy-fuel combustion or an electric arc (plasma). The molten particles are accelerated by the flame, followed by impacting onto a properly prepared substrate, usually metallic. Solidification occurs at rates akin to those obtained in Rapid Solidification Technology. Thus, the as-sprayed deposit is ultra-fine grained. Having the properties associated with such microstructures. The materials which are sprayed include most metal alloys and ceramics. In fact, virtually any material can be thermal sprayed as long as it does to decompose prior to melting. In this paper, we present a simple analytical mathematical model for the estimation of the maximum splat diameter of an impacting droplet on a subcooled target. The model uses an energy conservation argument, applied between the initial and final drop configurations, to approximately capture the dynamics of spreading. The effects of viscous dissipation, surface tension, and contact angle are taken into account. Tests against limited experimental data at high Reynolds and Weber numbers indicate that accuracy of the order of 5% is achieved. Also the effect of the spray angle on the maximum splat diameter can be calculated. Thus once the maximum splat diameter is found the thermal spraying process can be optimized for maximum efficiency. Various parameters like the initial droplet velocity, contact angle etc. can be pre-determined, thus making the process cost-efficient.